2023
DOI: 10.3390/v15020510
|View full text |Cite
|
Sign up to set email alerts
|

Plant Defense and Viral Counter-Defense during Plant–Geminivirus Interactions

Abstract: Geminiviruses are the largest family of plant viruses that cause severe diseases and devastating yield losses of economically important crops worldwide. In response to geminivirus infection, plants have evolved ingenious defense mechanisms to diminish or eliminate invading viral pathogens. However, increasing evidence shows that geminiviruses can interfere with plant defense response and create a suitable cell environment by hijacking host plant machinery to achieve successful infections. In this review, we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 160 publications
0
7
0
Order By: Relevance
“…Begomovirus proteins have been shown to target enzymes in the host methyl cycle or in DNA methylation pathways directly to repress methylation ( Wang et al., 2020 ; Gui et al., 2022 ). Suppression of TGS alters the methylation status of the host genome as well as viral DNA ( Gui et al., 2022 ; Zhang et al., 2023 ). Begomovirus infection has been associated with demethylation and activation of transposable elements in the host genome ( Gui et al., 2022 ; Guo et al., 2022 ) and similarly might activate the genomic copy of SEGS-1 in cassava.…”
Section: Discussionmentioning
confidence: 99%
“…Begomovirus proteins have been shown to target enzymes in the host methyl cycle or in DNA methylation pathways directly to repress methylation ( Wang et al., 2020 ; Gui et al., 2022 ). Suppression of TGS alters the methylation status of the host genome as well as viral DNA ( Gui et al., 2022 ; Zhang et al., 2023 ). Begomovirus infection has been associated with demethylation and activation of transposable elements in the host genome ( Gui et al., 2022 ; Guo et al., 2022 ) and similarly might activate the genomic copy of SEGS-1 in cassava.…”
Section: Discussionmentioning
confidence: 99%
“…In general, many studies have shown that C1 and C2 proteins encoded by different geminiviruses can suppress silencing (Table 1 and Figure 1). Being pathogenicity determinants of geminiviruses, both V2 and C4 proteins also exhibit VSR activity [215,[218][219][220][221][222][223][224][225][226][227][228].…”
Section: Order Geplafuvirales Family Geminiviridaementioning
confidence: 99%
“…To counteract this defense, the begomovirus genome encodes viral suppressors of RNA silencing (VSRs) [ 86 , 87 ]. Regarding begomoviral proteins associated with virus movement, V2 and C4 inhibit both transcriptional gene silencing (TGS) and posttranscriptional gene silencing (PTGS) [ 86 , 87 , 88 ]. V2 from cotton leaf curl Multan virus (CLCuMuV) effectively counteracts TGS by directly interacting with Argonaute 4 (AGO4) and suppressing RNA-dependent DNA Methylation (RdDM)-mediated TGS [ 89 ].…”
Section: Functions Of Movement Proteins In Suppression Of Host Defensesmentioning
confidence: 99%